Mehrjährige Beobachtungen über die Spiegel- und Salzgehaltschwankungen des Urmiasees - Plattner, Friedrich (ERDKUNDE, 1970)
The water level variations in Lake Urmia were recorded between 1951 and 1965. First order annual changes in surface level are superimposed over long periods on second order variations of changing, although important, extent. There are no grounds for supporting the opinion, widespread in Persia, that Lake Urmia is being subjected to a steadily progressive drying out. Changes in level are accompanied by reciprocal variations in the (significant) salt concentration. The results of this for the environmental conditions of plant and animal life (usufructuaries) are discussed.